(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The current research aims to demonstrate the impact of agile operations with their dimensions (leadership, culture, administrative communication) as an independent variable in the quality of banking service (reliability, response, guarantee, empathy, tangibility) as a dependent variable, in the Bank of Baghdad in Iraq, and to achieve the goal of the research, the researcher presented a framework A methodology for research and a comprehensive theoretical framework based on the latest sources that dealt with variables, and a field framework for analyzing and testing research hypotheses, by relying on the questionnaire as a basic tool for collecting data from the researched field. The researcher relied on the descriptive-analytical approach, through which the researcher tries to describe the phenomenon in question, for this the researcher relied on the comprehensive inventory method in determining the sample size, and then formulating a set of hypotheses that were statistically tested according to the statistical package (SPSS) program. She is one of the employees of the Bank of Baghdad, and the research sample was determined by (86) respondents, and the research reached several conclusions, the most important of which was the existence of a positive moral correlation between the variable Agile operations in their dimensions and the quality of banking service, and this relationship can be explained that the Bank of Baghdad’s interest in agile operations by focusing on activities of value and getting rid of activities that do not add any value and unnecessary and thus focus on efforts on the quality of service for the beneficiaries in the bank. The research presented a set of recommendations, the most important of which should be focus and work on developing and training employees in the bank on an ongoing basis on the concept and tools of agile operations so that they enjoy professional awareness, culture and sufficient awareness of various activities, procedures and developments in the business environment, especially accounting and the factors that may affect the quality of service provided in the bank.